Spatially controlled growth of highly crystalline ZnO nanowires by an inkjet-printing catalyst-free method. (11th February 2016) - Güell, Frank; Martínez-Alanis, Paulina R; Khachadorian, Sevak; Zamani, Reza R; Franke, Alexander; Hoffmann, Axel; Wagner, Markus R; Santana, Guillermo
Abstract: High-density arrays of uniform ZnO nanowires with a high-crystal quality have been synthesized by a catalyst-free vapor-transport method. First, a thin ZnO film was deposited on a Si substrate as nucleation layer for the ZnO nanowires. Second, spatially selective and mask-less growth of ZnO nanowires was achieved using inkjet-printed patterned islands as the nucleation sites on a SiO2 /Si substrate. Raman scattering and low temperature photoluminescence measurements were applied to characterize the structural and optical properties of the ZnO nanowires. The results reveal negligible amounts of strain and defects in the mask-less ZnO nanowires as compared to the ones grown on the ZnO thin film, which underlines the potential of the inkjet-printing approach for the growth of high-crystal quality ZnO nanowires.